Corticosteroid-induced immunosuppression ultimately does not compromise the efficacy of antibiotherapy in murine Mycobacterium ulcerans infection. - Teresa G Martins; Gabriela Trigo; Alexandra G Fraga; José B Gama; Adhemar Longatto-Filho; Margarida Saraiva; Manuel T Silva; António G Castro; Jorge Pedrosa (Public Library of Science (PLoS), 2012)
BACKGROUND: Buruli ulcer (BU) is a necrotizing disease of the skin, subcutaneous tissue and bone caused by Mycobacterium ulcerans. It has been suggested that the immune response developed during the recommended rifampicin/streptomycin (RS) antibiotherapy is protective, contributing to bacterial clearance. On the other hand, paradoxical reactions have been described during or after antibiotherapy, characterized by pathological inflammatory responses. This exacerbated inflammation could be circumvented by immunosuppressive drugs. Therefore, it is important to clarify if the immune system contributes to bacterial clearance during RS antibiotherapy and if immunosuppression hampers the efficacy of the antibiotic regimen. METHODOLOGY/PRINCIPAL FINDINGS: We used the M. ulcerans infection footpad mouse model. Corticosteroid-induced immunosuppression was achieved before experimental infection and maintained during combined RS antibiotherapy by the administration of dexamethasone (DEX). Time-lapsed analyses of macroscopic lesions, bacterial burdens, histology and immunohistochemistry were performed in M. ulcerans-infected footpads. We show here that corticosteroid-immunosuppressed mice are more susceptible to M. ulcerans, with higher bacterial burdens and earlier ulceration. Despite this, macroscopic lesions remised during combined antibiotic/DEX treatment and no viable bacteria were detected in the footpads after RS administration. This was observed despite a delayed kinetics in bacterial clearance, associated with a local reduction of T cell and neutrophil numbers, when compared with immunocompetent RS-treated mice. In addition, no relapse was observed following an additional 3 month period of DEX administration. CONCLUSIONS/SIGNIFICANCE: These findings reveal a major role of the RS bactericidal activity for the resolution of M. ulcerans experimental infections even during immunosuppression, and support clinical investigation on the potential use of corticosteroids or other immunosuppressive/anti-inflammatory drugs for the management of BU patients undergoing paradoxical reactions.